The Mediating Role of Work Engagement on the Influence of Leader-Member Exchange on Innovative Work Behavior (Study at PT. Bali Super Host) - Nengah Satria Prabawa Putra; Made Surya Putra (International Journal of Economics Accounting and Management, 2025)
Innovative work behavior is an innovative behavior starting from the creation, introduction, and application of new ideas deliberately in a job, group, or organization that aims to gain profits. This study aims to analyze and explain the role of work attachment mediation on the influence of leader-member exchange on innovative work behavior. This research was conducted at PT. Bali Super Host. The population in this study is 366 people. The number of samples used was 191 employees, with the method of determining samples of the Slovin technique. Data collection was obtained through questionnaires and interviews. The analysis techniques used are descriptive statistical analysis and inferential statistical analysis. The data was analyzed by Structural Equation Model (SEM) with the Partial Least Square (PLS) approach and using SmartPLS 3.0 software. The results of the study show that leader-member exchange has a positive and significant effect on work engagement and innovative work behavior, work engagement has a positive and significant effect on innovative work behavior. Work attachment partially mediates the influence of leader-member exchanges on innovative work behaviors. Companies need to pay attention to the implementation of leader-member exchanges and work engagement comprehensively so that innovative work behaviors in employees can be better implemented